Metaphyseal Core Decompression and Anterograde Fixation for Scaphoid Proximal Pole Fracture Nonunion without Avascular Necrosis - Rellan, Ignacio (J Wrist Surg, 2019)
Objective  To report the consolidation rate and the results of a series of 22 patients with metaphyseal core decompression of the distal radius and an antegrade compression screw. Methods  We present a prospective series of patients with scaphoid proximal pole nonunion in whom the presence of intraoperative bleeding was confirmed in both fragments. Patients with displacement, degenerative changes, fragmentation of the proximal pole, cavitation of the focus, loss of height, and necrosis, as well as those with carpal instability, were excluded. The patients were evaluated with X-rays and computed tomography to evaluate their consolidation; their mobility and fist strength were recorded and an analog visual scale (VAS) of pain at rest, pain in activity, subjective functional status, and DASH questionnaire were completed. Results  Of the 23 patients, 21 accomplished union. The average follow-up was 19 months and the average final range of motion was flexion 86%, extension 85%, radial deviation 79%, ulnar deviation 84%, and grip strength 84%. The average VAS for pain at rest was 1 point, the average VAS for activity pain was 2 points, the average VAS for function was 9 points, and the average DASH score was 8. Conclusions  Using this simple and reliable technique, we obtained 91% union and very good functional results. Metaphyseal core decompression of the distal radius associated with an antegrade scaphoid screw is a reasonable and effective option for the treatment of proximal pole scaphoid nonunions without avascular necrosis in carefully selected patients. Level of Evidence  This is Level IV study.